Penyuluhan dan Sosialisasi Peningkatan Kapasitas Pengelola Dalam Mitigasi Risiko di Desa Wisata Cibuntu, Kabupaten Kuningan - Rahmat Ingkadijaya; Surya Fadjar Budiman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
This service activity aims to improve the competence of Cibuntu Tourism Village managers in mitigating risks from natural and non-natural risk sources in tourist villages. The method used in this activity is counseling and socialization. The number of participants in this activity was 21 people. This activity is beneficial for Cibuntu Village which is required to be more professional in managing its tourist village because it is able to mitigate risks both from natural sources (such as natural disasters), and non-natural so as to ensure safety. and the safety of guests visiting the Cibuntu Tourism Village.